Experiences of adults with intellectual disabilities on the right to independent living: A case study - Vega Córdova, Vanessa.; Álvarez Aguado, Izaskun.; González Carrasco, Félix.; Spencer González, Herbert.; Jarpa Azagra, Marcela.; Exss Cid, Katherine. (Centro Interamericano de Investigaciones Psicológicas y Ciencias Afines, 2023)
In the field of intellectual disability, the development of an independent life has been configured as a human and civil right that allows these people to articulate desired life plans. Despite the advances, at the international level, research on aspects related to independent living in people with intellectual disabilities continues to be very scarce. Generally, the approaches to the study of this construct are based on broader investigations dedicated to evaluating the levels of quality of life or self-determination of this population in residential services or sheltered housing. Precisely, this study analyzes, through a case study, the meanings that an advisory group made up of eight adults with intellectual disabilities has on the concept of independent living in the Chilean context in order, on the one hand, to identify relevant elements for the definition of the construct from the perceptions and experiences of this population; and on the other, to propose guidelines at various levels that allow progress in the realization of this right. To collect the data, a semi-structured group interview was designed whose questions were grouped around four themes: previous conceptions of the participants about the construct of independent life, satisfaction with life and possibilities of the context for the development of personal independence, role of family, friendship and partner in independent life, and opportunities of the work context for the achievement of personal independence. During the interview, another strategy was incorporated in which visual language gained more relevance. Specifically, a set of ten mood-boards were used that allowed participants to delve into the different topics addressed. The results of the code validation process were calculated using Krippendorff’s alpha statistics (.954) and Cohen’s kappa (.953), which showed a high level of inter-judge agreement. As a result of this process, categories (N = 6) and subcategories (N = 17) were established. The results show how various needs, barriers and facilitators for the development of independent life are identified from the interviews of the interviewees. Among the main needs is the performance of a paid work activity or the establishment of solid affective relation-ships. With regard to the barriers that hinder personal independence, the most notorious are related to the difficulty of being financially independent or to the lack of accessibility in the work environment. Regarding the elements that facilitate the development of an independent life, the role of the couple stands out as a constant figure of support for independence and personal empowerment. These results suggest some guidelines for planning interventions on this construct. Among others, they should seek the acquisition of skills that strengthen the self-care capacity of this group; should promote increased opportunities for making meaningful choices in the workplace, personal and community; and they must adapt to the spaces in which people with intellectual disabilities operate in adulthood. On the other hand, it is assumed that one of the main limitations of this research is that the results are not generalizable. However, this study has some strengths. Among others, it contributes to enriching the bulk of research on independent living, this being an aspect barely addressed in the literature. It also complements the results of other research regarding the elements that can condition the development of skills for personal independence. This allows for the design of interventions that provide opportunities for independent living based on the felt needs of these people. In addition, it raises future lines of research related, for example, to the importance of the informed choice of the residential environment or to the study of the possibilities of the digital world as an incident phenomenon in the acquisition of skills for personal independence.
Experiencias de personas adultas con discapacidad intelectual sobre el derecho a la vida independiente: Un estudio de caso
Keywords: Autopercepciones; Discapacidad intelectual; Vida independiente; Adultos